PENGARUH LAMA PENYIMPANAN TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) DALAM MENGENDALIKAN HAMA KUTU DAUN PERSIK (Myzus persicae Sulzer) (Homoptera: Aphididae) PADA TANAMAN CABAI (Capsicum annuum L.) - Rustam, Rusli; Laoh, Jeltje Hennie; ', Alfindra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Myzus persicae Sulzer (Homoptera: Aphididae) is one of a major pest that attack red chili plants (Capsicum annuum L.). Farmers usually use a synthetic insecticides to controll Myzus persicae, which has many negative effects. One of the alternative controll that can be used to minimize the effect of synthetic insecticides is Piper aduncum L. which is formulated in powder. The research was conducted in Plant Pest Laboratory and Laboratory of Integrated Pest Management, Faculty of Agriculture, University of Riau. Research used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments are betel leaf powder 75 g/l of water with variation S0 (without storage), S1 (1 month storage), S2 (2 months storage), S3 (3 months storage). The results showed that the betel leaf powder without storage (S0) had better results than other treatments. This treatment has a fastest time of initial death 9.80 hours, LT50 reach in 29.20 hours and total mortality 89%.   Keywords: Capsicum annuum L., Myzus persicae Sulzer, Piper aduncum L.